Bidirectional association between periodontitis and type 2 diabetes mellitus: a literature review (Research, Society and Development, 2021)
The link that periodontitis has with systemic diseases such as type 2 diabetes mellitus (T2DM) has been studied for a long time. Current evidence suggests that the mechanisms underlying this link are related to the inflammatory mediators present in both diseases and indicates that both diseases represent a mutual risk factor for developing each disease, respectively. Likewise, the impact that periodontal treatment can have on T2DM has been extensively studied, which could develop new treatment guidelines for this metabolic disease. However, this situation is currently not clear despite the clinical studies that have been carried out. It is suggested that such treatment can improve glycemic control and complications related to diabetes. The objective of this present review is to inform about the possible pathophysiological mechanisms that link T2DM with periodontitis in a bidirectional way. In the same way, to approach in a general way the effect that periodontal treatment can have on control of T2DM.